Code-Mixing Used by Alexandra Asmasoebrata in Volix Media Youtube Channel - Putrawan, I Wayan; Widhiarcani Matradewi, Ni Ketut; Aryani, I Gusti Agung Istri (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2024)
Sociolinguistics is the study that concerns the relation between society and language use. The part of sociolinguistics that is code-mixing The study aims at (1) identifying the types, and (2) defining the factors of code mixing used by Alexandra Asmasoebrata on the Volix Media YouTube Channel. The focused of the study is on code mixing Indonesian-English. The data was collected by Volix Media YouTube channel. This study employs a qualitative research methodology, and the observation method is the data collection strategy. Hoffman's (1991) theory is used to analyze the many forms and factors of code mixing. This study shows that there are 11 utterances were used by Alexandra Amasoebrata on the Volix Media Youtube channel that contained code-mixing. 4 data for intra-sentential, 2 data for intra-lexical. The factor found in the data source is 2 data for talking about a particular topic, 1 data for repetition used for clarification, the intention of clarifying the speech content for interlocutor is 1 data, and being emphatic about something (expressing solidarity) is 1 data. Keywords: Sociolinguistic, Code-mixing, Youtube